Optimizing the palm sugar industry through the implementation of appropriate technology - Oesman Raliby Al-Manan; Alfan Bahrul Alim; Muhammad Bintang Hilali; Muhammad Fiki Nasrulloh; Firmansyah Ibnu Murtadlo; Muhammad Syarif Hidayatullah (Community Empowerment, 2021)
The potential of palm sugar in Ngancar, Candimulyo, Magelang Regency is broad and labor-intensive, guaranteed to reduce the urbanization level. Since production is manual, it requires more time and energy. This Integrated Community Service (PPMT) activity aims to diffuse production process technology to partners through technology transfer and provide motivation for entrepreneurship. Rapid Rural Appraisal (RRA) is the method used by the PPMT group in developing/empowering rural communities and especially in observing the partner conditions extensively, quickly, and efficiently. The design of appropriate technology for the palm sugar sieving machine is one of the product outputs produced by the group during the mentoring period. They also created entrepreneurial motivation for the assisted partners. Conclusively, the results proved that the utilization of appropriate technology accelerates the completion time of the production process in a more cost-effective manner.